Rancang Bangun Mesin Pemotong Stik Kentang dengan Penggerak Motor - Sir Anderson; Dian Wahyu; Andrianto Andrianto; Fedri Hidayat (Jurnal Teknik Mesin, 2024)
Potatoes are one of Indonesia's horticulture products and are among the top five global staple foods. Indonesian MSMEs still use manual manufacturing technologies to produce potato sticks. Due to limited production capacity and short production times, this business faces significant challenges. After identifying the issues, an idea emerged to create a motor-driven tool capable of cutting potato sticks. The manufacturing of potato stick-cutting tools is expected to enhance business efficiency. This potato stick-cutting machine has a capacity of 336 kg/hour, a potato shear stress of 0.006 N/mm2, a working cutting force of 132 N, and a motor power of 33.84 watts.